Pengaruh Upaya Peningkatan Kompetensi Diri dan Pengalaman Mengajar Terhadap Kinerja Guru Ekonomi SMA di Kabupaten Tulungagung - Titis Dwi Prastika; Wahjoedi Wahjoedi (Jurnal Pendidikan Ekonomi, 2022)
Teacher performance is a determining factor in learning which will affect student learning outcomes. Improving teacher performance can be done by increasing factors that influence it, one of which is internal factors such as competence and field experience. The purpose of this study is to analyze the effect of efforts to increase self-competence and teaching experience on teacher performance partially or simultaneously. This research was conducted in high schools throughout Tulungagung Regency at the end of March to April 2022 with data collection techniques through questionnaires and obtained 39 samples from 45 populations. The analysis technique uses multiple linear regression with SPSS software version 22.0. The results of the analysis show that efforts to increase self-competence have a positive and significant effect on teacher performance while the teaching experience variable has no significant effect on teacher performance, but simultaneously efforts to increase self-competence and teaching experience have a significant positive effect on teacher performance. So it can be concluded that no matter how much teaching experience you have when you do not participate in activities to improve self-competence, the performance you have is meaningless.DOI: https://dx.doi.org/10.17977/UM014v15i22022p114